MRI-based analysis of the microstructure of the thalamus and hypothalamus and functional connectivity between cortical networks in episodic cluster headache - Chiara Abagnale; Antonio Di Renzo; Giada Giuliani; Gabriele Sebastianelli; Francesco Casillo; Lucia Ziccardi; Vincenzo Parisi; Cherubino Di Lorenzo; Mariano Serrao; Francesca Caramia; Vittorio Di Piero; Gianluca Coppola (The Journal of Headache and Pain)
Abstract Background Neuroimaging studies have shown that hypothalamic/thalamic nuclei and other distant brain regions belonging to complex cerebral networks are involved in cluster headache (CH). However, the exact relationship between these areas, which may be dependent or independent, remains to be understood. We investigated differences in resting-state functional connectivity (FC) between brain networks and its relationship with the microstructure of the hypothalamus and thalamus in patients with episodic CH outside attacks and healthy controls (HCs). Methods We collected 3T MRI data from 26 patients with CH during the in-bout period outside the attacks and compared them with data from 20 HCs. From resting-state data we derived independent component (IC) networks. We calculated the fractional anisotropy (FA) and mean (MD), axial (AD), and radial (RD) diffusivity values of the hypothalamus and bilateral thalami and correlated them with resting-state IC Z-scores and CH clinical features. Results Patients with CH had less FC between the salience network (SN) and left executive control network (ECN) than HCs, but more FC between the default mode network and right ECN. Patients with CH showed lower FA and higher MD microstructural hypothalamic metrics than HCs. Patients with CH had a higher bilateral FA metric in the thalamus than HCs. The AD and RD diffusivity metrics of the hypothalamus were positively correlated with the disease history duration. We found no correlations between the hypothalamic and thalamic diffusivity metrics and the FC of the cortical networks. Conclusion Our findings presented the possibility of a correlation between the FC of the SN and the inability to switch between internalizing and externalizing brain activity during demanding cognitive tasks, such as recurring headaches. Moreover, we found differences in the thalamic and hypothalamic microstructures that may independently contribute to the pathophysiology of CH. These differences may reflect changes in directional organization, cell size, and density.